Lead free solder joint thermal condition in semiconductor packaging - Harif, Muhammad Najib; Nadzri, Allina; Jusoff, Kamaruzaman (Science Publications, 2010)
Solder joints are responsible for both electrical and mechanical connections. Solder does not have adequate ductility to ensure the repeated relative displacements due to the mismatch between expansion coefficients of the chip carrier and the circuit board. Solder material plays a crucial role to provide the necessary electrical and mechanical interconnections in an electronic assembly. Finding a technique to increase the service life of future connections is not the total solution. A method must be developed for predicting the remaining service life of many joints already in use. Approach: The effect of High Temperature Storage (HTS) on lead free solder joint material for ball grid array application using pull test method is studied in this study. Some statistical analysis base on the pull test data also discussed. Three samples of different lead free solder joint material were selected in this experiment namely Sn3.8Ag0.7Cu (SAC387), Sn2.3Ag0.08Ni0.01Co(SANC) and Sn3.5Ag. After the thermal condition test, all the lead free solder joint material samples were tested using Dage 4000 pull test machine. Each pull test will be 5 units and each unit contains 8balls. Results: The mean pull strength for high temperature storage is 2847.66, 2628.20 and 2613.79 g for Sn3.5Ag, SANC and SAC387, respectively. Thus, Sn3.5Ag shows a significantly better solder joint performance in terms of joint strength compare to SANC and SAC387. Hence, Intermetallic Compound (IMC) thicknesses were measured after cross-sectioning. Sample size for cross-sectioning was 3 units per read point, 2 balls per unit and 3 maximum IMC peaks per ball and the measurement using high power scope of 100x and Image Analyzer software to measure the IMC thickness. For high temperature storage, result show that the mean IMC thicknesses for SAC387, SANC and Sn3.5Ag are 3.9139, 2.3111 and 2.3931 μm. Conclusion/Recommendations: It was found that IMC thickness for SANC and Sn3.5Ag does not show significant growth after high temperature storage but SAC387 demonstrated significant growth Lower intermetallic thickness implies less brittle joint effect, thus from this part of study, better joint reliability is expected for the Sn3.5Ag solder system.